(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
• Shokirov, T. F. (2025). Kredit-modul sharoitida bo‘lajak boshlang‘ich sinf o‘qituvchilarining mustaqil ishlashga oid kasbiy kompetentligini rivojlantirish. Ta’lim, Fan va Innovatsiya jurnali, 2025/02, • Шокиров T. . (2025). МЕТОДЫ РАЗВИТИЯ ПРОФЕССИОНАЛЬНОЙ КОМПЕТЕНТНОСТИ БУДУЩИХ УЧИТЕЛЕЙ НАЧАЛЬНЫХ КЛАССОВ. Предпринимательства и педагогика, 3(4), 105–114. извлечено от https://inlibrary.uz/index.php/entrepreneurship-pedagogy/article/view/59431Abdullaeva M., Kholbekov S., Mahmudov A. “Pedagogical technologies and interactive methods”. –Tashkent: Teacher, 2019. • Karimov I.A. “A well-rounded generation is the foundation of Uzbekistan’s development”. –Tashkent: Sharq, 1997. • Utayev S., Khoshimov N. “Teaching methods”. –Tashkent: Fan, 2020. • Hasanboyeva O., Yuldoshev M. “Theory and practice of pedagogical technologies”. –Tashkent: Noshir, 2018. • Norkulov K., Abdullayev R. “Interactive educational technologies”. –Samarkand: SamSU, 2021. • Vahobov A., Rakhimov M. “Innovative approaches in the teaching process”. –Tashkent: Yangi asr avlod, 2017.